Furtive majesty in John Ford’s Perkin Warbeck - John Gillies (Sillages Critiques)
In Ford’s Perkin Warbeck, a charismatic and virtuous pretender is opposed an uncharismatic and unvirtuous monarch, Henry VII. To Perkin, his title is as good as Henry’s. Thus he patterns his invasion of England on that of Henry’s own previous invasion to rid England of Richard III – a tyrant whom Henry is now imagined as resembling. In Bacon’s History of Henry VII, however, Henry’s Machiavellianism is taken to be acceptable in regard of its effectiveness. Yet where for Bacon Henry’s legitimacy is undiminished, for Ford it is severely compromised and especially by comparison with the virtuous and charismatic Perkin. One root of this opposition, I suggest, is a tension between the Stuart tendency to vest divine right in the monarch’s person, and the protestant parliamentary vision of a polity-centred kingship (oddly reminiscent of Henry’s actual monarchical practice). This tension converges on the word ‘majesty’. Eleven years after the publication of Ford’s play, Charles would be condemned in parliamentary propaganda for abandoning Westminster and his majesty to wander aimlessly about the country like Perkin Warbeck.